2022
DOI: 10.1093/cid/ciac489
|View full text |Cite
|
Sign up to set email alerts
|

Increased Deaths From Fungal Infections During the Coronavirus Disease 2019 Pandemic—National Vital Statistics System, United States, January 2020–December 2021

Abstract: Background COVID-19–associated fungal infections cause severe illness, but comprehensive data on disease burden are lacking. We analyzed US National Vital Statistics System (NVSS) data to characterize disease burden, temporal trends, and demographic characteristics of persons dying from fungal infections during the COVID-19 pandemic. Methods Using NVSS’s January 2018–December 2021 Multiple Cause of Death Database, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…and Candida spp. [ 34 ]. Poor data are available on non-COVID-19 patients admitted during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…and Candida spp. [ 34 ]. Poor data are available on non-COVID-19 patients admitted during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…and Candida spp.—was observed. [ 20 ]. In this context, the development of new strategies to manage fungal infections is crucial—especially for infections caused by fungi resistant to classic antifungal drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on reports of fungal secondary infections in COVID-19 patients, we examined patients prior to the RECOVERY publication to assess the potential impact of glucocorticoid use. [8][9][10][11] Two recent meta-analyses of randomized trials found consistent benefits of steroids in COVID-19 without any major adverse effects. 5,12 However, the reports acknowledged uncertainty about adverse event rates due to variable definitions and inconsistent reporting of serious adverse effects across studies.…”
Section: Introductionmentioning
confidence: 99%